Analysis of failure in patients with adenoid cystic carcinoma of the head and neck. An international collaborative study. Issue 7 (26th October 2013) - Amit, Moran; Binenbaum, Yoav; Sharma, Kanika; Ramer, Naomi; Ramer, Ilana; Agbetoba, Abib; Miles, Brett; Yang, Xinjie; Lei, Delin; Bjøerndal, Kristine; Godballe, Christian; Mücke, Thomas; et al.
Abstract Background Adenoid cystic carcinoma (ACC) is a locally aggressive tumor with a high prevalence of distant metastases. The purpose of this study was to identify independent predictors of outcome and to characterize the patterns of failure. Methods An international retrospective review was conducted of 489 patients with ACC treated between 1985 and 2011 in 9 cancer centers worldwide. Results Five‐year overall‐survival (OS), disease‐specific survival (DSS), and disease‐free survival (DFS) were 76%, 80%, and 68%, respectively. Independent predictors of OS and DSS were: age, site, N classification, and presence of distant metastases. N classification, age, and bone invasion were associated with DFS on multivariate analysis. Age, tumor site, orbital invasion, and N classification were independent predictors of distant metastases. Conclusion The clinical course of ACC is slow but persistent. Paranasal sinus origin is associated with the lowest distant metastases rate but with the poorest outcome. These prognostic estimates should be considered when tailoring treatment for patients with ACC. © 2013 Wiley Periodicals, Inc. Head Neck 36: 998–1004, 2014